The Effect of Microstructural Changes in Nickel-Based Alloys on Their Corrosion Resistance in Molten Halides: A Consideration of Prospective Structural Materials for Molten Salt Reactors - Anastasia I. Trubcheninova; Aleksander V. Abramov; Ruslan R. Alimgulov; Ilya B. Polovov; Vladimir A. Volkovich (Applied Sciences)
Corrosion of nickel alloys in molten salts is a complex process dependent on many factors. The paper describes the influence of microstructural changes in several nickel-based alloys (Hastelloy® G-35®, VDM® Alloy 59, KhN62M-VI, Hastelloy® B-3®) on the mechanism of their corrosion in molten fluoride salts. The corrosion experiments were performed in LiF–NaF–KF and (LiF–NaF–KF) + UF4 melts at 550–750 °C. Formation of excess secondary phases along the grain boundaries of the alloys led to heterogeneity of the alloy microstructure. As a result of these changes, microgalvanic couples formed on the surface of the alloys, leading to the development of intergranular corrosion upon contact with molten electrolytes. Secondary phases acted as microanodes or microcathodes depending on a number of factors. Formation and composition of the secondary phases affected the depth and extent of the corrosion damage to nickel alloys.